2015
DOI: 10.1002/uog.14786
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic resonance imaging‐estimated placental perfusion in fetal growth assessment

Abstract: ObjectiveTo evaluate in‐vivo placental perfusion fraction, estimated by magnetic resonance imaging (MRI), as a marker of placental function.MethodsA study population of 35 pregnant women, of whom 13 had pre‐eclampsia (PE), were examined at 22–40 weeks' gestation. Within a 24‐h period, each woman underwent an MRI diffusion‐weighted sequence (from which we calculated the placental perfusion fraction), venous blood sampling and an ultrasound examination including estimation of fetal weight, amniotic fluid index a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
25
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 40 publications
(31 citation statements)
references
References 33 publications
4
25
0
Order By: Relevance
“…We reported a mean placental perfusion fraction of 29%, indicating that the microvascular compartment of the placenta remained consistently highly perfused during mid‐ and late‐gestation. This value is congruent with the report of Moore et al, who found a mean f of 26% and is also close to the placental f of 32% in healthy pregnancies reported by Sohlberg et al Our findings also match closely the f of the central placenta (35.1%) reported in a previous study and is lower than the mean value (42.5%) reported by Siauve et al, although our observed perfusion fraction is significantly lower than the perfusion values of the decidua basalis reported in normal and small for gestational age subjects . The perfusion fraction as previously found to be a sensitive marker of decreased placental perfusion in murine models and in human studies, and our study confirms the generally accepted range of normal placental perfusion fraction in the central parts of the placenta by means of IVIM.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…We reported a mean placental perfusion fraction of 29%, indicating that the microvascular compartment of the placenta remained consistently highly perfused during mid‐ and late‐gestation. This value is congruent with the report of Moore et al, who found a mean f of 26% and is also close to the placental f of 32% in healthy pregnancies reported by Sohlberg et al Our findings also match closely the f of the central placenta (35.1%) reported in a previous study and is lower than the mean value (42.5%) reported by Siauve et al, although our observed perfusion fraction is significantly lower than the perfusion values of the decidua basalis reported in normal and small for gestational age subjects . The perfusion fraction as previously found to be a sensitive marker of decreased placental perfusion in murine models and in human studies, and our study confirms the generally accepted range of normal placental perfusion fraction in the central parts of the placenta by means of IVIM.…”
Section: Discussionsupporting
confidence: 93%
“…27 The results of Derwig et al 21 are in line with these findings, as they investigated a relatively narrow gestational age range of 24 to 29 weeks, when, according to Siauve et al, f remains stable. 27 On the contrary, Sohlberg et al 26 reported a significant decrease of f with gestational age. We found a moderate correlation between placental f and gestational age, with increasing values over gestation.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…This technique assumes that blood motion is incoherent over a voxel and of higher degree than surrounding tissue . The IVIM technique has been applied to placenta imaging in healthy subjects and demonstrated promise in detecting differences in the perfusion fraction in pregnancies with fetal growth restriction, small for gestational age fetuses, and in early and late preeclampsia compared with controls. In initial comparisons of placental perfusion, IVIM demonstrated a higher predictive power to reduced birthweight than ASL FAIR .…”
Section: Discussionmentioning
confidence: 99%
“…The perfusion of maternal blood in the human placenta, so called placental perfusion , has a crucial role for the effective delivery of nutrients and gases to the fetus 1 . Any impedance to blood flow through the placenta compromises placental perfusion, and ultimately compromises the provision of necessary nutrients to the growing fetus 2 . Therefore, placental perfusion may be used as an early biomarker of placental dysfunction associated with fetal growth restriction (FGR).…”
Section: Introductionmentioning
confidence: 99%